Characterisation of target antigen of cell-mediated immunity in Mycobacterium tuberculosis H37RV - Hattikudur, Sandhya; Kamat, R. S. (Journal of Medical Microbiology, 1984)
SUMMARY Antigen participating in cell-mediated immunity was isolated from a sonic extract of Mycobacterium tuberculosis H37Rv. The purified antigen had a mol. wt 150000-200 000, based upon its Rf in 7.5% polyacrylamide gel in the presence of sodium dodecyl sulphate. In simple agarose gel electrophoresis it had an Rf of 0.85. The protein in its native state was identified in the sonic extract with an antiserum to the purified antigen; it too had an Rf of 0.85 in agarose gel electrophoresis. The purified antigen elicited a delayed hypersensitivity response and stimulated the generation of activated macrophages in mice immunised with M. tuberculosis H37Rv.